1986
DOI: 10.1017/s0003356100018328
|View full text |Cite
|
Sign up to set email alerts
|

Inter-breed relationship of maintenance efficiency to milk yield in cattle

Abstract: As part of a multibreed cattle project for studying genetic variation between breeds, four adult females from each of five breeds of cattle were kept for up to 2 years in a non-pregnant, non-lactating state on each of four feeding levels. The breeds, which were Hereford, Aberdeen Angus, Dexter, British Friesian and Jersey, provided a wide range of genetic potential for body size and milk yield. The feeding levels were arranged to make the weight of lipid in the whole body about 0·05, 0·15, 0·25 and 0·35 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
7

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 27 publications
3
30
2
7
Order By: Relevance
“…In our case, mice selected for greater maintenance requirements have demonstrated greater milking ability and are the same size. Taylor et al (1986) compared maintenance requirements of low and high milking breeds of cattle. They found that beef breeds had lower maintenance requirements than those of dual-purpose breeds.…”
Section: Resultsmentioning
confidence: 99%
“…In our case, mice selected for greater maintenance requirements have demonstrated greater milking ability and are the same size. Taylor et al (1986) compared maintenance requirements of low and high milking breeds of cattle. They found that beef breeds had lower maintenance requirements than those of dual-purpose breeds.…”
Section: Resultsmentioning
confidence: 99%
“…For example, breeders may be interested in increasing the growth rate of progeny till weaning and during fattening. However, exclusive selection on increased growth rates will often result in higher mature weight as well (Taylor et al, 1986). As a consequence, selection of bulls for a high growth rate in a performance test has resulted in increased mature weight of dairy and beef cows in recent decades.…”
Section: Definition Of Traits Characterising the Growth Potential Of mentioning
confidence: 99%
“…Diferenças genéticas podem ocasionar mudanças de 20 a 30% nos requerimentos, sendo a característica moderada a altamente herdável (Taylor & Young, 1968). Entre diferentes raças, ocorrem correlações positivas do nível de exigência de energia de mantença com o potencial gené-tico de produção de leite e com a taxa de crescimento (Ferrell & Jenkins, 1985;Taylor et al,1986) Parte das diferenças nas exigências de mantença entre raças deve-se a variações nos tamanhos relativos dos tecidos ou órgãos do corpo. A atividade metabólica da proteína corporal é muito mais intensa que a do tecido adiposo, o que tende a elevar as exigências de energia de mantença, por unidade de tamanho metabólico, em animais com maiores proporções de músculos ou de menor maturidade fisiológica (Garrett,1980).…”
Section: Introductionunclassified